2011
DOI: 10.1002/apj.448
|View full text |Cite
|
Sign up to set email alerts
|

Modification of epoxidised canola oil

Abstract: Epoxidation of canola oil was carried out using a peroxyacid generated in situ from hydrogen peroxide and a carboxylic acid (acetic or formic acid) in the presence of liquid inorganic acid, H 2 SO 4 , as catalyst. Acetic acid was found to be a better oxygen carrier than formic acid as it gave about 11% more conversion of ethylenic unsaturation to oxirane than that given by formic acid under otherwise identical conditions. A high temperature of above 65• C is significantly unfavourable for achieving high oxiran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…51 The use of peroxyformic acid to epoxidize vegetable oils unsaturation has been treated in different articles. 29,30,32,39,40 Goud et al 29 and Dinda et al 39 have used a reactor immersed in a water bath system, and did not consider the energy balance. They have observed that the epoxidation was faster with PFA than with PAA but the use of PFA was less selective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 The use of peroxyformic acid to epoxidize vegetable oils unsaturation has been treated in different articles. 29,30,32,39,40 Goud et al 29 and Dinda et al 39 have used a reactor immersed in a water bath system, and did not consider the energy balance. They have observed that the epoxidation was faster with PFA than with PAA but the use of PFA was less selective.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32] Establishing the mass balance only on the organic phase and assuming steady-state approach on peroxycarboxylic acids formation. 13,[33][34][35][36][37][38][39][40] The advantage of that approach is that graphical method can be used to determine epoxidation rate constants, but one neglects ring-opening reaction. This model is called homogeneous model.…”
mentioning
confidence: 99%
“…A comparison of the life cycles and the environmental impact of soy‐ and petro‐based polyols has also been discussed . Usually, vegetable‐oil‐based polyol synthesis is a two‐step process, in which the first step is the epoxidation of unsaturated vegetable oil fatty acids or fatty esters . The second step of the process is the subsequent reaction of the epoxy groups, which usually involves two or more hydroxyl‐group‐containing reactants and acid catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cai et al [78] and Mungroo et al [79] found a value of 10.3 and 10.7 kcal/mol, using soybean and canola oil as raw material, respectively. There is a small diference among these values and our determined one (7.3 kcal/mol).…”
Section: Kinetic Model For the In Situ Epoxidation Of Grape Seed Oilmentioning
confidence: 99%